In situ stress measurement method of deep borehole based on multi-array ultrasonic scanning technology - Wang, Jinchao; Wang, Chuanying; Huang, Junfeng; Han, Zengqiang; Zeng, Wenhao; Wang, Yiteng (Frontiers in Earth Science, 2022)
As scientific research continues to focus on the deep part of the earth, the measurement of deep in-situ stress is becoming more and more important. In order to improve the accuracy and efficiency of deep in-situ stress measurement, based on the widespread hole wall collapse in deep drilling, a deep borehole in-situ stress measurement method based on multi array element ultrasonic scanning technology is proposed in this paper. The solution idea of using the combination of multiple array elements for borehole contour scanning is put forward, and a multi array element ultrasonic scanning technology suitable for fine horizontal section scanning of deep geological borehole contour is formed. Through the analysis of the calculation principle of hole wall caving method and the derivation of multi array element ultrasonic scanning solution algorithm, a multi array element ultrasonic scanning device is developed by using the effective fusion of multi array element ultrasonic full waveform scanning signals and the reconstruction of horizontal section contour. The measurement method of in-situ stress in deep drilling combined with hole wall caving method is studied. Finally, the feasibility and accuracy of this method are verified by physical experiments. The results show that: the effective fusion of multi array ultrasonic full waveform scanning signals and horizontal section contour reconstruction can break through the limitations of conventional in hole probe placement and in hole medium sound velocity calibration, and improve the fine reconstruction and accurate measurement of 360° wall shape; The multi array element ultrasonic scanning technology can obtain the hole shape data at any depth of the borehole, and then obtain the measurement of the three-dimensional shape of the borehole wall. It has the feasibility of theory, method and technology in the borehole wall caving in-situ stress measurement, and provides a new technical means for the three-dimensional detection of the borehole wall and in-situ stress measurement.